RECONSTRUCTING THE HADITH TRADITION OF MINANGKABAU: Bibliography, Codicology, and Intellectual Networks in the Surau Taram Manuscripts - Afriadi, Afriadi; Saputra, Rafiko; Riza, Yulfira; Wendry, Novizal (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
The intellectual tradition of Minangkabau demonstrates that surau served not merely as ritual spaces but also as intellectual institutions that played a vital role in the transmission, interpretation, and production of hadith knowledge. This study examines six hadith manuscripts from Surau Taram to reconstruct their bibliographical structure, codicological features, and epistemological significance within the wider Islamic scholarly networks of the Malay–Indonesian world. Employing a qualitative descriptive approach, the research combines manuscript metadata analysis, codicological examination of digital images, and thematic mapping based on the EAP352/5 collection of the British Library. The findings reveal that the manuscripts, written on eighteenth- and nineteenth-century European paper bearing Pro Patria and HNH watermarks, exhibit dense textual layouts, red-and-black rubrication, and pedagogical annotations, indicating their use as working texts in advanced hadith instruction. Thematically, they integrate discussions of fada’il, ethics, and ritual jurisprudence, reflecting a distinctive surau-based epistemology that differs from the traditions of Javanese pesantren and Acehnese dayah. These findings affirm the position of Surau Taram as a regional intellectual center linked to trans-local networks of Islamic scholarship. Furthermore, the study highlights the urgency of preserving these manuscripts through high-resolution digitization, codicological standardization, and future comparative research with manuscripts from the Haramain. Tradisi intelektual Minangkabau menunjukkan bahwa surau tidak hanya berfungsi sebagai ruang ritual, tetapi juga sebagai institusi intelektual yang memainkan peran penting dalam transmisi, interpretasi, dan produksi pengetahuan hadis. Penelitian ini mengkaji enam manuskrip hadis dari Surau Taram untuk merekonstruksi struktur bibliografis, karakteristik kodikologis, dan signifikansi epistemologisnya dalam jaringan keilmuan Islam yang lebih luas di kawasan Melayu–Indonesia. Dengan menggunakan pendekatan deskriptif kualitatif, penelitian ini mengintegrasikan analisis metadata manuskrip, pemeriksaan kodikologis terhadap citra digital, serta pemetaan tematik berdasarkan koleksi EAP352/5 milik British Library. Temuan penelitian menunjukkan bahwa manuskrip-manuskrip tersebut, yang ditulis pada kertas Eropa abad ke-18 dan ke-19 dengan cap air Pro Patria dan HNH, menampilkan tata letak teks yang padat, rubrikasi merah–hitam, serta anotasi pedagogis yang mengindikasikan penggunaannya sebagai teks kerja dalam pengajaran hadis tingkat lanjut. Dari segi tematik, manuskrip-manuskrip tersebut memadukan pembahasan mengenai fada’il, etika, dan fikih ibadah, yang mencerminkan epistemologi khas berbasis surau yang berbeda dari tradisi pesantren di Jawa maupun dayah di Aceh. Temuan ini menegaskan posisi Surau Taram sebagai pusat intelektual regional yang terhubung dengan jaringan transregional keilmuan Islam. Selain itu, penelitian ini menyoroti urgensi pelestarian manuskrip-manuskrip tersebut melalui digitalisasi beresolusi tinggi, standardisasi kodikologi, serta pengembangan penelitian komparatif dengan manuskrip-manuskrip Haramain pada masa mendatang.